Computerized Grading System for Peñafrancia Elementary School (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Using a well-innovated, computerized, and friendly user grading system is very compatible for Peñafrancia Elementary School. Hence, the researchers developed a system that will help the teachers to help them because every year the student’s on that particular school are always increasing and that is the main reason why the process of their grading gets slow because of managing the time off limit of the teacher that can’t handle the time of being rush. For an innovative system, the researcher uses the waterfall method or the systems development life cycle method. First, the researchers gathered information according to the plans and a unique strategy. As a result, the researchers found out what are the problems the client are facing. Those gathered data and information were compressed and combined to form ideas and after that proceed to the next step which is the system design, implementation, or implementing of the project, then the researchers proceed to the testing with the client. And proceed to the development of the project, and lastly for the maintenance of the system that was scheduled. The system and all the gathered information may be enough to result in a succession of the project system. But if it is not successful, better try harder and search for improvements. Gain more knowledge of the essentials of the project. If the planned success, then the students of BCP (Bestlink College of the Philippines) will have the ability to develop a system that Peñafrancia Elementary School enables to use a grading system. In the first place, the researchers choose the Peñafrancia Elementary School as a client to help eliminate the manual process of computing grades that causes hassle and difficulties for the teacher. Grading and reporting of cards are phenomena that need a component throughout recording all the data depending on the student’s performance. It refers to the generalization of getting the proponents of the grades that will release to the parents. The Metropolitan Academy conduct a study about the Grading system same project that the researchers conducted. The MA has a more complicated system, first, the Teachers encode all the student’s information then it will compute next.
Keywords: Bestlink College of the Philippines,Metropolitan Academy, systems development life cycle, Peñafrancia Elementary School, University of Cape Coast